2020
DOI: 10.1103/physrevresearch.2.042007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple spin-orbit excitons and the electronic structure of αRuCl3

Abstract: The honeycomb compound α-RuCl 3 is widely discussed as a proximate Kitaev spin-liquid material. This scenario builds on spin-orbit entangled j = 1/2 moments arising for a t 5 2g electron configuration with strong spin-orbit coupling λ and a large cubic crystal field. The actual low-energy electronic structure of α-RuCl 3 , however, is still puzzling. In particular, infrared absorption features at 0.30, 0.53, and 0.75 eV seem to be at odds with a j = 1/2 scenario. Also the energy of the spin-orbit exciton, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(106 reference statements)
4
16
1
Order By: Relevance
“…Very recently the spin-orbit excitation spectrum in α-RuCl 3 was investigated by Raman spectroscopy mainly focussing on the thickness dependence of the electronic structure utilizing exfoliated samples starting from bulk down to the mono-layer regime [75]. In thicker samples the authors observed two well-separated peaks at 249 and 454 meV, which they ascribe in accordance with the work of Warzanowski et al [56], as single and double spin orbiton. Astonishingly, both peaks remain visible down to the monolayer thickness and both excitations exhibit a continuous red shift on decreasing thickness.…”
Section: Subgap Electronic Excitationssupporting
confidence: 68%
See 1 more Smart Citation
“…Very recently the spin-orbit excitation spectrum in α-RuCl 3 was investigated by Raman spectroscopy mainly focussing on the thickness dependence of the electronic structure utilizing exfoliated samples starting from bulk down to the mono-layer regime [75]. In thicker samples the authors observed two well-separated peaks at 249 and 454 meV, which they ascribe in accordance with the work of Warzanowski et al [56], as single and double spin orbiton. Astonishingly, both peaks remain visible down to the monolayer thickness and both excitations exhibit a continuous red shift on decreasing thickness.…”
Section: Subgap Electronic Excitationssupporting
confidence: 68%
“…This conclusion is in agreement with recent x-ray absorption results [52] providing a value of 12 meV for the splitting of the excited quartet. This spin-orbit excitation has been analysed in much more detail by Warzanowski et al [56]. Their analysis yields a SOC constant λ ∼ 175 meV and a value of the trigonal splitting of order 60 meV.…”
Section: Subgap Electronic Excitationsmentioning
confidence: 95%
“…Starting from this insulating antiferromagnetic ground state, the only phases that can be reached by tuning the temperature are a paramagnetic insulator or a paramagnetic metal. Owing to their inherently intertwined degrees of freedom, correlated materials can display excitons that, unlike their analog in band insulators, couple to spin and orbital degrees of freedom 2 , 3 or form more exotic composite quasiparticles 4 . Therefore, driving these excitons with light offers a playground for exploring many-body phenomena beyond the physics of band insulators, especially the promise of reaching new phases of matter.…”
Section: Introductionmentioning
confidence: 99%
“…It implies a spin-orbit coupling constant λ = 2∆ SOC /7 = 71 meV [43], smaller by ≈20 meV than the a 2u -e u splitting and by a factor of ≈4.4 than the a 2u -a ′ 2u splitting in Table II. This λ is actually weaker than the corresponding parameter of, e. g., Ru 3+ 4d 5 ions on the Kitaev honeycomb lattice of α-RuCl 3 [44,45].…”
mentioning
confidence: 78%